Supercomputing and Numerical Techniques in Astrophysis Fluid Flow Modelling - Carapau, Fernando (2008)
Computational astrophysics is a central part of modern research on Astrophysics. Computer simulations have become an indispensable tool for studying astrophysical problems. This training school brings together, for the first time in Europe, graduate students, postdoctoral researchers and experienced European computational physicists and astrophysicists to discuss an integrated overview of the numerical and computational techniques that are most adequate to model different astrophysical fluid flow phenomena by means of supercomputing simulations. The participants will attend theoretical and laboratory courses and one workshop per week on computational Astrophysics (see details below). On the third week the participants will develop a computational project that will make use of the supercomputer facility at the University of Coimbra. Travel, accommodation and living expenses of both the participants are covered by the organization. Each of the partner institutions will select up to 6 participants (among graduate students and post-doctoral researchers) per country including their own institution. Any interested applicant to attend the school should contact the responsible for the selection process at each country according to the countries.